Variation in Anatomical Position of Vermiform Appendix - Maria Yousaf, Shumaela Kanwal, Anum Nawazish Ali, Ayesha Ali, Nadia Ahmad, Ammara Ghafoor (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Delaying acute appendicitis diagnosis may cause appendix perforation and abscess or peritonitis. Appendectomy is one of the most common surgeries in Pakistan, however little is known about vermiform appendix variation architecture. Hence, appendix anatomy may improve prognosis, this research identified appendix anatomical locations, length, and age and sex relationships. Objective: This study aimed to identify the anatomical sites of the appendix, the length of the appendix and to examine the associations between these factors and age and sex. Study Design: Retrospective cross-sectional study Study Setting: This study was conducted in anatomy department of Islamic International Medical College, Rawalpindi from August 2022 to January 2023. Methodology: This retrospective cross-sectional research was completed in the (department and hospital name) between (year). This study was approved from Ethical review committee with IRB (no). The patients reports were taken for the completion of the study. The CT scan of both gender from 8 to 60 years with the help radiologist suggestions were included in this study. Together with a radiologist, we analyzed CT axial images, a coronal of 1.5 mm thickness, and a sagittal reconstruction to assess the anatomical findings of the vermiform appendix retrospectively. Results: There were 300 total participants in this research, 165 (55%) were female and 135 (45%) were male between 8years to 60 years of age. In both sexes, the following sites were found Pelvic, Post ileal, Pre ileal, Retro caecal, Retro colic, Retro Para colic, and Sub caecel. Appendix length and site was shown to be significantly different in gender and age (p<0.001). Children less than 10 years old were more likely to have an incomplete mesoappendix. According to our findings, males have a longer appendix than females do. On the other hand, we discovered that the appendix tends to become longer with age. Practical implication: The location of the appendix reportedly varies among ethnic and geographical groups. Preoperative planning requires knowledge of these variations. Although appendectomy is one of the most common operations in Pakistan, very little is known about vermiform appendix variation anatomy in the country. Conclusion: This study’s findings showed that the vermiform appendix is most often seen in the pelvic position on CT in the Karachi-based population. In conclusion, the high prevalence of anterior location and full mesoappendix in our group suggests that acute appendicitis may be more easily and quickly diagnosed in our demographic, with fewer instances of sequelae including perforation and gangrene. Keywords: Vermiform Appendix, Pelvic, Post ileal, Pre ileal, Retro caecal, Retro colic, Retro Para colic, and Sub caecel